An update on the diagnosis and treatment of diabetic somatic and autonomic neuropathy [version 1; referees: 3 approved] - Shazli Azmi (F1000Research, 2019)
Diabetic peripheral neuropathy (DPN) is the most common chronic complication of diabetes. It poses a significant challenge for clinicians as it is often diagnosed late when patients present with advanced consequences such as foot ulceration. Autonomic neuropathy (AN) is also a frequent and under-diagnosed complication unless it is overtly symptomatic. Both somatic and autonomic neuropathy are associated with increased mortality. Multiple clinical trials have failed because of limited efficacy in advanced disease, inadequate trial duration, lack of effective surrogate end-points and a lack of deterioration in the placebo arm in clinical trials of DPN. Multifactorial risk factor reduction, targeting glycaemia, blood pressure and lipids can reduce the progression of DPN and AN. Treatment of painful DPN reduces painful symptoms by about 50% at best, but there is limited efficacy with any single agent. This reflects the complex aetiology of painful DPN and argues for improved clinical phenotyping with the use of targeted therapy, taking into account co-morbid conditions such as anxiety, depression and sleep disturbance.